2009
DOI: 10.1194/jlr.m800402-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized LDL impair adipocyte response to insulin by activating serine/threonine kinases

Abstract: Oxidized LDL (oxLDL) increase in patients affected by type-2 diabetes, obesity, and metabolic syndrome. Likewise, insulin resistance, an impaired responsiveness of target tissues to insulin, is associated with those pathological conditions. To investigate a possible causal relationship between oxLDL and the onset of insulin resistance, we evaluated the response to insulin of 3T3-L1 adipocytes treated with oxLDL. We observed that oxLDL inhibited glucose uptake (240%) through reduced glucose transporter 4 (GLUT4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 109 publications
2
31
1
1
Order By: Relevance
“…Moreover, oxLDL and 7κ-C were also reported to impair (pre) adipocyte differentiation and induce IR in mature adipocytes [104,117,118]. On the other hand, as previously mentioned, oxysterols can also behave as antiadipogenic signals by diverting pluripotent mesenchymal cells′ fate away from adipogenic and in favor of the osteogenic lineage through transactivation of Wntmediated signaling pathway [90,104,119].…”
Section: Oxysterolsmentioning
confidence: 87%
“…Moreover, oxLDL and 7κ-C were also reported to impair (pre) adipocyte differentiation and induce IR in mature adipocytes [104,117,118]. On the other hand, as previously mentioned, oxysterols can also behave as antiadipogenic signals by diverting pluripotent mesenchymal cells′ fate away from adipogenic and in favor of the osteogenic lineage through transactivation of Wntmediated signaling pathway [90,104,119].…”
Section: Oxysterolsmentioning
confidence: 87%
“…Using murine 3T3-L1 adipocytes, Scazzocchio et al (2009) showed that Ox-LDL can cause the impairment of insulin signalling likely because of insulin receptor substrate-1 degradation through enhanced Ser 307 phosphorylation. On the other hand, there is increasing evidence that Ox-LDL induces beta cell dysfunction and reduction of insulin production (Maziere et al 2004, Abderrahmani et al 2007, Favre et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that there is a clear connection between oxidative stress and development of type 2 diabetes mellitus (T2DM) that is related to insulin resistance. First, several reports showed increased plasma OxLDL levels in the metabolic syndrome as well as in T2DM and obesity (248). It is also known that hyperglycemia induces nonenzymatic oxidation of a variety of lipids and proteins.…”
Section: Oxldl In Diabetes Mellitusmentioning
confidence: 99%
“…in this process is OxLDL-induced impairment of glucose transporter 4 (GLUT4) (248). This transporter is stored in intracellular vesicles in insulin-sensitive cells like adipocytes and myocytes and translocates to the plasma membrane upon stimulation by insulin.…”
Section: Oxldl In Diabetes Mellitusmentioning
confidence: 99%